Correction to: Clinically relevant phenotypes in chronic rhinosinusitis - Jessica W. Grayson; Marina Cavada; Richard J. Harvey (Journal of Otolaryngology - Head and Neck Surgery)
Following publication of the original article [1], the authors reported an error in Table 1. In the second columns of the ‘Radiology’ row, ‘Normal anterolateral sinus mucosa’ should read ‘Normal superolateral sinus mucosa’. A corrected version of Table 1 is included in this Correction.